ION MICROPROBE INVESTIGATION OF PLAGIOCLASE AND ORTHOPYROXENE FROM LUNAR MG-SUITE NORITES: IMPLICATIONS FOR CALCULATING PARENTAL MELT REE CONCENTRATIONS AND FOR ASSESSING POSTCRYSTALLIZATION REE REDISTRIBUTION - Papike J.J.; Fowler G.W.; Shearer C.K.; Layne G.D. (My University, 1996)
The lunar Mg-suite, which includes dunites, troctolites, and norites, makes up to 20-30% of the Moon's crust down to a depth of #60 km. The remainder is largely anorthosite. This report focuses on norites (which consist mostly of orthopyroxene and plagioclase) because we have found that both phases are effective recorders of their parental melt compositions. In an earlier report, we analyzed orthopyroxene from twelve samples (three from Apollo 14, two from A-15, and seven from A-17) by SIMS for eight REE (La, Ce, Nd, Sm, Eu, Dy, Er, Yb). Inversion of these data to estimated melt compositions yielded extremely high REE concentrations similar to KREEP. In this study, we report SIMS REE data for plagioclase from these same twelve samples. The major objective of this study is to estimate parental REE concentrations from both orthopyroxene and plagioclase data to see if both data inversions produce concordant melt compositions and thus better constrain the composition of melts parental to Mg-suite norites. The estimated REE concentrations from both phases show some evidence of slight postcrystallization REE redistribution. Comparison of the observed ratio of REE forpyroxeneplagioclase to the ratio of the Ds for pyroxeneplagioclase is consistent with REE redistribution which involves LREE diffusing from pyroxene into plagioclase and HREE diffusing from plagioclase into pyroxene. However, apparently these postcrystallization exchanges have not seriously affected our ability to estimate melt REE concentrations. The estimated melt REE concentrations using both plagioclase and orthopyroxene, are similar to high-K KREEP especially for melts parental to A-15 norites. This study provides support for mineral trace element inversion estimates for parental melts. Even though these lunar crustal lithologies experienced high temperature annealing, apparently the cores of plagioclase and pyroxene continue to carry a record of their igneous crystallization history.